2016
DOI: 10.1111/jeb.13019
|View full text |Cite
|
Sign up to set email alerts
|

Medullary bone in fossils: function, evolution and significance in growth curve reconstructions of extinct vertebrates

Abstract: Medullary bone (MB) is a special endosteal tissue forming in the bones of female birds during egg laying to serve as a labile calcium reservoir for building the hard eggshell. Therefore, the presence of MB reported in multiple nonavian dinosaurs is currently considered as evidence that those specimens were sexually mature females in their reproductive period. This interpretation has led to further inferences on species-specific growth strategies and related life-history aspects of these extinct vertebrates. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 184 publications
(348 reference statements)
2
43
0
2
Order By: Relevance
“…As the possible cause of this notably thick ICL has not been discussed in these taxa, it remains unclear whether the extremely thick femoral ICL is pathological or a characteristic feature of the species Jeholornis curvipes . However, a medullary bone origin for this structure is very unlikely, as it lacks the characteristic high porosity and woven bone content of medullary bone 96 , 97 .…”
Section: Discussionmentioning
confidence: 99%
“…As the possible cause of this notably thick ICL has not been discussed in these taxa, it remains unclear whether the extremely thick femoral ICL is pathological or a characteristic feature of the species Jeholornis curvipes . However, a medullary bone origin for this structure is very unlikely, as it lacks the characteristic high porosity and woven bone content of medullary bone 96 , 97 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chinsamy and Tumarkin-Deratzian 18 showed that tissues remarkably similar to MB occur in some pathological avian bones. Finally, Prondvai and Stein 15 , Chinsamy and colleagues 13 , and Prondvai 19 have reported MBL with unknown functionality in non-pathological and presumably non-reproductive (rapidly growing, juvenile) dinosaurs and pterosaurs. These issues show that caution should be exercised before concluding that MB reflecting sex and reproductive status is truly present in fossils 15 , 18 20 .…”
Section: Introductionmentioning
confidence: 98%
“…The identification of MB in non-avian fossil archosaurs as a means to determine sex and reproductive activity was based on three histological characteristics: (1) location in the medullary cavity; (2) an endosteal origin, marked by a resorption line between the cortex and the hypothetical MB; and (3) a woven arrangement of the collagen fibers, suggesting rapid bone deposition. Given the factors noted above that can produce MBL, these criteria in and of themselves cannot differentiate MB from MBL 18 , 19 . Hence, some past identifications of MB may be incorrect 12 , 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in circulating hormone levels appear to play an important role in triggering medullary bone formation. Studies focusing on four species belonging to the orders Galliformes, Anseriformes, and Columbiformes have found that elevated estrogen levels stimulate medullary bone formation (Table 1), and it has been presumed that this is the case across the Aves and their recent ancestors (e.g., Prondvai, In press). Yet, these studies reflect a small subset of avian diversity (Fig.…”
Section: Introductionmentioning
confidence: 99%